Dampak Perdagangan Lintas Batas TerhadapmPerekonomian Masyarakat Lokal di Wilayah Perbatasan Wini - Timor Leste - Yasinta Nuban; Fransina W. Ballo; Maria Indriani Hewe Tiwu (Journal Of Business, Finance, and Economics (JBFE), 2024)
Cross-border trade is the activity selling goods between residents of different countries in border areas on the basis of mutual agreement. TTU district is one of the districts that borders directly with Timor Leste, especially the Oecusse enclave district. The research aims to explain the impacts of cross-border trade on the economy of local communities in the Wini-Timor Leste border area. This research is descriptive qualitative in nature with the data collection technique in the research being triangulation using the data analysis method proposed by Miles and Huberman. The results of the research show that cross-border trade between Wini and Timor Leste has an impact on the local economy such as increasing income, creating jobs which reduces the unemployment rate, infrastructure development, improving community welfare and also relational relations between the people of Wini and Timor Leste remain intact. However, there are also negative impacts that need to be addressed, such as unequal income distribution, unhealthy competition between local communities, security challenges and rapid socio-cultural changes.